The assimilation of Western medicine into a semi-nomadic healthcare system: A case study of the indigenous Aeta Magbukún, Philippines - Balilla, V.; Anwar McHenry, Julia; McHenry, M.; Parkinson, R.; Banal, D. (Springer New York LLC, 2014)
The Aeta Magbukún are a genetically and culturally distinct group of Indigenous people living in an isolated mountain forest in the municipality of Mariveles, in the province of Bataan, Philippines. This research aims to document some healthcare related information of the people, inform future decisions regarding maximising benefits of modern conveniences, and minimise negative consequences on their culture and health. Using an ethnographic approach, data were collated from a community health survey in combination with field notes from three of the co-authors while living with the Aetas. Despite major implications from rapid ecological and cultural changes, traditional ethnomedical systems continue to be revered as an essential healing practice, although they are increasingly used in conjunction with Western medicines and healthcare. At the Aeta village level, the changing socio-political influence among the kagun (traditional healer), the NGOs, and the Municipal Council in terms of healthcare provision is pivotal, as the kagun has chosen to integrate the Western medicine and healthcare services into their traditional healthcare system, without simply rejecting them. In turn, Western-style healthcare interventions have the potential to be carefully managed to integrate traditional Aeta Magbukún socio-political structures, healthcare, and cultural continuity. The cumulative influence of numerous other novel aspects to Aeta life (e.g., permanent housing, a highway through the village, literacy, cash economies, energy-dense foods, communication/entertainment devices, etc.) will place additional pressure on the traditional ethnomedical healthcare system. However, enabling the continuity of access to appropriate healthcare knowledge (both the transfer of knowledge from Western medicine to the Aeta Magbukún, and vice versa) can assist many cultures through the inherent stresses of increasingly rapid acculturation and development. © 2014 International Association for Ecology and Health.